Kebutuhan E-LKPD Sejarah Lokal Kota Padang Periode Revolusi Fisik untuk Siswa di SMA - Rahma Sagita; Ridho Bayu Yefterson (Jurnal Kronologi, 2023)
This study is part of a phase of development studies using the ADDIE model. This article describes the needs analysis phase of a development study being conducted. The purpose of this study was to identify the needs of the Student Worksheet (LKPD) as a learning resource in SMAN 7 Padang based on the stages of needs analysis conducted. The data collection method used in this study was by observation and interview. The obtained data were analyzed in four steps: 1) data analysis, 2) data reduction, 3) data display, and 4) data validation. The discussion and results of this study, on the premise that there is a problem with the history teaching and learning process, proceed as follows. 1) Student Analysis: Students need learning resources that can enhance their understanding of local history. 2) Teacher Analysis, A teacher needs learning resource in her E-Student Worksheets (LKPD) that focuses on local history. 3) Curriculum analysis of learning outcomes and history learning Indicators based on the E-Student Worksheets (LKPD) developed as high school history learning resources.